KEDUDUKAN LEMBAGA NEGARA DALAM MAKAN BERGIZI GRATIS - Denok Oktawila; Himawan Estu Bagijo; Tanudjaja Tanudjaja (Lembaga Dongan Dosen, 2025)
The free nutritious meal program is a plan to provide nutritious meals in schools or Islamic boarding schools to improve students' nutrition. Estimated number of beneficiaries (nationally) of the free nutritious meal program for 514 districts/cities with a total of 16,110,000 million school children. The aim of this research is to determine the application of Pancasila values through the free nutritious meal program. This research uses the Systematic Literature Review (SLR) method by identifying, reviewing, evaluating, and interpreting available research to be used as a data source. The aim of the free nutritious meal program launched by the government is closely related to the fifth principle of Pancasila, namely